+0  
 
0
378
3
avatar

Can someone explain substitution method when there are more than two parts?

 

ie) 9m - 2n - 42 = 0 and 5m - 2n - 26 = 0

Guest Apr 8, 2017

Best Answer 

 #1
avatar+7641 
+2

Can someone explain substitution method when there are more than two parts?
ie)

\( 9m - 2n - 42 = 0 \)

and

5m - 2n - 26 = 0

 

\(9m - 2n - 42 = 0 \\m= \color{red}\frac{2n+42}{9}\)     

 

\(5m - 2n - 26 = 0\\5({\color{red}\frac{2n+42}{9}})-2n-26=0\\10n+210-18n-234=0\\-8n=24\\{\color{blue}n=-3}\)         [ substitute  \(m=\color{red}\frac{2n+42}{9}\)

 

\(9m - 2n - 42 = 0 \\9m-2(-3)-42=0\\9m=42-6\\m= \frac{36}{9}\\\color{blue}m=4\)

 

laugh  !

asinus  Apr 8, 2017
edited by asinus  Apr 8, 2017
 #1
avatar+7641 
+2
Best Answer

Can someone explain substitution method when there are more than two parts?
ie)

\( 9m - 2n - 42 = 0 \)

and

5m - 2n - 26 = 0

 

\(9m - 2n - 42 = 0 \\m= \color{red}\frac{2n+42}{9}\)     

 

\(5m - 2n - 26 = 0\\5({\color{red}\frac{2n+42}{9}})-2n-26=0\\10n+210-18n-234=0\\-8n=24\\{\color{blue}n=-3}\)         [ substitute  \(m=\color{red}\frac{2n+42}{9}\)

 

\(9m - 2n - 42 = 0 \\9m-2(-3)-42=0\\9m=42-6\\m= \frac{36}{9}\\\color{blue}m=4\)

 

laugh  !

asinus  Apr 8, 2017
edited by asinus  Apr 8, 2017

7 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.